Application of Switchable Hydrophobicity Solvents for Extraction of Emerging Contaminants in Wastewater Samples - Salazar-Gonzalez, R; Toledo-Neira, C; Toledo-Neira, C (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In the present work, the effectiveness of switchable hydrophobicity solvents (SHSs) as extraction solvent (N,N-Dimethylcyclohexylamine (DMCA), N,N-Diethylethanamine (TEA), and N,N-Benzyldimethylamine (DMBA)) for a variety of emerging pollutants was evaluated. Different pharmaceutical products (nonsteroidal anti-inflammatory drugs (NSAIDs), hormones, and triclosan) were selected as target analytes, covering a range of hydrophobicity (LogP) of 3.1 to 5.2. The optimized procedure was used for the determination of the target pharmaceutical analytes in wastewater samples as model analytical problem. Absolute extraction recoveries were in the range of 51% to 103%. The presented method permits the determination of the target analytes at the low ng mL-1 level, ranging from 0.8 to 5.9 (except for Triclosan, 106 ng mL-1) with good precision (relative standard deviation lower than 6%) using high-pressure liquid chromatography (HPLC) combined with ultraviolet (DAD) and fluorescence (FLR) detection. The microextraction alternative resulted in a fast, simple, and green method for a wide variety of analytes in environmental water sample. The results suggest that this type of solvent turns out to be a great alternative for the determination of different analytes in relatively complex water samples. © 2019 by the authors.